Complementary Therapies To Reduce Fatigue In Hemodialysis Patients: A Scoping Review Of Randomized Controlled Trials - Syarief Hidayatullah Bahri; Eko Mardiyaningsih (Borneo Nursing Journal (BNJ), 2025)
Fatigue is one of the most common symptoms experienced by hemodialysis patients and has a negative impact on their quality of life, functional ability, and psychological condition. This scoping review aims to map the latest scientific evidence on the effectiveness of complementary therapies in reducing fatigue among hemodialysis patients based on Randomized Controlled Trials (RCTs) published between 2020 and 2025. The review followed the Joanna Briggs Institute (JBI) and PRISMA-ScR guidelines. Literature searches were conducted across five databases (PubMed, ProQuest, Sage Journals, BMC Journals, and Google Scholar) using MeSH-based keywords and Boolean operators. Inclusion criteria included RCTs involving hemodialysis patients aged ≥18 years, interventions involving complementary therapies such as physical exercise, massage, acupressure, relaxation, humor, or digital-based interventions, and fatigue as the primary outcome. From 3,355 identified articles, eight studies met the inclusion criteria and were further analyzed. Thematic synthesis identified six complementary interventions consistently effective in reducing fatigue: intradialytic physical exercise, olive oil massage, acupressure combined with Qur’anic murrotal recitation, relaxation techniques (autogenic, deep breathing, Benson), humor therapy, and digital recreational therapy. All interventions reported statistically significant reductions in fatigue (p < 0.05) and improvements in psychological well-being and patient comfort. Complementary therapy shows strong potential as a safe, low-cost, and effective non-pharmacological strategy to alleviate fatigue in hemodialysis patients. Further research is recommended to assess long-term effectiveness, develop standardized operational procedures, and explore implementation within Indonesian healthcare contexts.